2017
DOI: 10.1007/978-3-319-67687-6_33
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pointing with Pointer Acceleration

Abstract: In this paper we investigate the dynamics (including velocities and accelerations) of mouse pointing when Pointer Acceleration (PA) functions are used. We also propose a simple model for these dynamics from a control theoretic perspective. The model allows us to simulate the effect of PA functions on pointing dynamics. In particular, it reproduces and explains many important phenomena we observe in pointing dynamics with PA functions. These include: (1) Pointer position, velocity, and acceleration over time, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This phenomenon is also seen in pointing motion across various interfaces, i.e. HCI using a mouse 29 . The human adopts a two-phase mechanism to fulfill the pointing motion, the surge phase and the corrective phase.…”
Section: Benefit and Limitation Of The Vite Modelmentioning
confidence: 79%
See 1 more Smart Citation
“…This phenomenon is also seen in pointing motion across various interfaces, i.e. HCI using a mouse 29 . The human adopts a two-phase mechanism to fulfill the pointing motion, the surge phase and the corrective phase.…”
Section: Benefit and Limitation Of The Vite Modelmentioning
confidence: 79%
“…Mouse pointer movements have been extensively studied in the literature 23,[29][30][31] . Given the wand and blimp trajectories from experiments, we analyze the blimp movements when interacting with the human.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Data Preprocessing: It has been shown that when human performs the pointing motion, the pointer velocity data is noisy [29]. To address this issue, we filter the wand velocity using a Savitzky-Golay filter with a 4th order polynomial and a window size of 81 (8 secs), and calculate the smoothed wand trajectory by integrating the filtered velocity.…”
Section: Experiments Setting and Data Processingmentioning
confidence: 99%
“…Mouse pointer movements have been extensively studied in the literature [23,[29][30][31]. Given the wand and blimp trajectories from experiments, we analyze the blimp movements when interacting with the human.…”
Section: Background: Vite Modelmentioning
confidence: 99%
“…Another second-order model resembling a spring-mass-damper system (second order lag) was recently used in [29] to examine pointing dynamics in reciprocal pointing with pointer acceleration.…”
Section: Introductionmentioning
confidence: 99%